Quality planning and analysis: from product development through use - Juran, J.M.; Gryna, Frank M. (New Delhi: Tata McGraw-Hill, 1980)
this comprehensive, proven book shows how every facet of planning and operating in the production and service facilities of a company contributes to the level of quality in goods and services. Existing material on managerial, engineering and statistical topics is retained, with additional stress on engineering topics. Highly readable, it is a must for professional and students in quality control, industrial and production engineering and quality management.
Basic concepts -- Quality costs -- Probability distributions -- Statistical aids for analyzing data -- Quality improvement-management-controllable defects -- Quality improvement-operator-controllable defects;motivation for quality -- Designing for quality -- Designing for quality- Statistical aids -- Vendor relation-statistical aids -- Manufacture -- Manufacture-statistical aids -- Manufacture-process control concepts -- Manufacture-process control techniques -- Inspection and test;product acceptance -- Measurement -- Acceptance sampling -- Customer relations -- Field use and quality -- Field use and quality-statistical aids -- Consumer relation,product safety, and liability -- Quality assurance -- Policies and objectives -- Organization for quality -- Quality information systems
Incudes index
Keywords: Quality management; Quality control; Quality analysis